Understanding energy saving and CO2 reduction in wastewater treatment plants. (17th March 2011) - Hao, X.D.; Qiu, F.G.; Van Loosdrecht, M.C.M.
Wastewater Treatment Plants (WWTPs) have to deal with the issue of energy saving and/or CO2 reduction. Aeration, sludge return, chemical dosing, sludge reduction, sludge digestion, etc. could indeed have some function on this issue. On the other hand, controlled processes of COD and nutrient conversions could also be of benefit to the issue. With this paper, the relationship between energy consumption and CO2 emission is firstly analysed. Applicable technologies of energy recovery via sludge are then evaluated. Finally, the function of denitrifying dephosphatation on energy saving and CO2 reduction is demonstrated by modelling simulations.